2006
DOI: 10.1029/2005jb003727
|View full text |Cite
|
Sign up to set email alerts
|

Spatial‐temporal patterns of seismic tremors in northern Cascadia

Abstract: [1] We study in detail the two consecutive episodic tremor-and-slip (ETS) events that occurred in the northern Cascadia subduction zone during 2003 and 2004. For both sequences, the newly developed Source-Scanning Algorithm (SSA) is applied to seismic waveform data from a dense regional seismograph array to determine the precise locations and origin times of seismic tremors. In map view, the majority of the tremors occurred in a limited band bounded approximately by the surface projections of the 30-km and 50-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
143
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(159 citation statements)
references
References 38 publications
16
143
0
Order By: Relevance
“…LFEs are only rarely identified in regions with tremor outside of Japan (e.g. Kao et al, 2006, Sweet et al, 2008. It is unclear if this difference represents a real variation in tremor activity or simply a limitation in the observation capabilities of networks outside of Japan.…”
Section: Fundamental Properties Of Tremormentioning
confidence: 96%
See 1 more Smart Citation
“…LFEs are only rarely identified in regions with tremor outside of Japan (e.g. Kao et al, 2006, Sweet et al, 2008. It is unclear if this difference represents a real variation in tremor activity or simply a limitation in the observation capabilities of networks outside of Japan.…”
Section: Fundamental Properties Of Tremormentioning
confidence: 96%
“…Within an individual ETS episode, highlysimilar bursts of tremor repeat many times, suggesting that tremor radiates from an individual location many times . From ETS episode to ETS episode, tremor also typically occurs in the same locations Kao et al, 2006), whereby much of the area where tremor occurs is the same from event to event. Ambient tremor occurring outside ETS events is typically found in these same locations as well.…”
Section: Fundamental Properties Of Tremormentioning
confidence: 99%
“…Recently it is found that LF events take place constantly in the uppermost mantle under the non-volcanic areas in western Japan, possibly related to the dehydration reactions of the subducting Philippine Sea plate (e.g., Ide et al, 2007;Ito et al, 2007;Obara, 2009;Schwartz and Rokosky, 2007;. Such LF events are also found to occur in the forearc region of other subduction zones, such as Cascadia (Kao et al, 2006;Schwartz and Rokosky, 2007). It is generally considered that the LF events reflect the fluid and magmatic activities in the crust and uppermost mantle under a tectonically active region.…”
Section: Introductionmentioning
confidence: 96%
“…In Cascadia, when the multibeam-backprojection method is applied to the array data (Ghosh et al, 2012), nearly continuous tremor activities were detected. The array-based results provide detailed spatiotemporal evolutions of tremor activities when compared with the network-based methods, such as the WECC method (e.g., Wech and Creager, 2008), the source-scanning algorithm (Kao et al, 2006), and the waveform-matching technique (Shelly et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%